Management System in Fish Market using Mobile Application - Ku, Zhi Kang; RAMLI, AZIZUL AZHAR (Applied Information Technology And Computer Science, 2021)
The management system in fish market using mobile application is a system which act as an online market platform that user can buy sea products and the seller can manage the products through the application. With the rapid development of the mobile application, digital devices such as mobile phone and the tablet have been more widely to use in daily life. But the fish markets in Sungai Rengit still use a manual filling system which is record book to handle the records in market and it is not efficiency. All the price of the products is not stated clearly and causing customer confuse on the price of products. The application is developed by using Android Studio. The JAVA and XML languages are used to develop the application with the object-oriented development methodology. The application allow seller to manage the fish market by manage the products and check the orders from customers. Besides, the application allows users to view the sea products, they can add the product to cart and make an online payment. They also can edit their profile and search the products. At the end of this project, management system in fish market application provides a good and efficiency service to the user and seller. The application is environment friendly and easily to be used.